Clinical determinants and neural correlates of presbyphagia in community-dwelling older adults - Labeit, Bendix; Muhle, Paul; von Itter, Jonas; Slavik, Janna; Wollbrink, Andreas; Sporns, Peter; Rusche, Thilo; Ruck, Tobias; Hüsing-Kabar, Anna; Gellner, Reinhold; Gross, Joachim; Wirth, Rainer; et al. (Frontiers in Aging Neuroscience, 2022)
Background: “Presbyphagia” refers to characteristic age-related changes in the complex neuromuscular swallowing mechanism. It has been hypothesized that cumulative impairments in multiple domains affect functional reserve of swallowing with age, but the multifactorial etiology and postulated compensatory strategies of the brain are incompletely understood. This study investigates presbyphagia and its neural correlates, focusing on the clinical determinants associated with adaptive neuroplasticity. Methods: 64 subjects over 70 years of age free of typical diseases explaining dysphagia received comprehensive workup including flexible endoscopic evaluation of swallowing (FEES), magnetoencephalography (MEG) during swallowing and pharyngeal stimulation, multidimensional sarcopenia diagnostics, laboratory analyses, and assessment of nutritional status, frailty, olfaction, cognition and mental health. Neural MEG activation was compared between participants with and without swallowing impairment in FEES, and associated clinical influencing factors were analyzed. Results: Half of the participants showed swallowing impairment, mainly characterized by pharyngeal residue, whereas the airway was rarely compromised. In the MEG analysis, participants with presbyphagia activated an increased cortical sensorimotor network during swallowing. As major clinical determinant, participants with swallowing impairment exhibited reduced pharyngeal sensation. Presbyphagia was an independent predictor of a reduced nutritional status. Conclusions: Swallowing alterations frequently occur in otherwise healthy older adults and are associated with decreased nutritional status. Increased sensorimotor cortical activation constitutes a compensation attempt to uphold swallowing function due to sensory decline. The original concept of presbyphagia, in which age-related swallowing changes are considered physiological per se, may need to be expanded into a theory with a continuous transition between presbyphagia and dysphagia.